A Phase I clinical trial of EUS-guided intratumoral injection of the oncolytic virus, HF10 for unresectable locally advanced pancreatic cancer - Hirooka, Yoshiki; Kasuya, Hideki; Ishikawa, Takuya; Kawashima, Hiroki; Ohno, Eizaburo; Villalobos, Itzel B.; Naoe, Yoshinori; Ichinose, Toru; Koyama, Nobuto; Tanaka, Maki; Kodera, Yasuhiro; Goto, Hidemi (BMC cancer, 2018)
Prognosis of pancreatic cancer is poor with a 5-year survival rate of only 7%. Although several new chemotherapy treatments have shown promising results, all patients will eventually progress, and we need to develop newer chemotherapy treatments to improve response rates and overall survival (OS). HF10 is a spontaneously mutated oncolytic virus derived from a herpes simplex virus-1, and it has potential to show strong antitumor effect against malignancies without damaging normal tissue. We aimed to evaluate the safety and anti-tumor effectiveness in phase I dose-escalation trial of direct injection of HF10 into unresectable locally advanced pancreatic cancer under endoscopic ultrasound (EUS)-guidance in combination with erlotinib and gemcitabine administration. The mid-term results have been previously reported and here we report the final results of our study. This was a single arm, open-label Phase I trial. HF10 was injected once every 2 weeks and continued up to four times in total unless dose-limiting toxicity (DLT) appears. A total of nine subjects in three Cohorts with dose-escalation were planned to be enrolled in this trial. The primary endpoint was the safety assessment and the secondary endpoint was the efficacy assessment. Twelve patients enrolled in this clinical trial, and ten subjects received this therapy. Five patients showed Grade III myelosuppression and two patients developed serious adverse events (AEs) (perforation of duodenum, hepatic dysfunction). However, all of these events were judged as AEs unrelated to HF10. Tumor responses were three partial responses (PR), four stable diseases (SD), and two progressive diseases (PD) out of nine subjects who completed the treatment. Target lesion responses were three PRs and six SDs. The median progression free survival (PFS) was 6.3 months, whereas the median OS was 15.5 months. Two subjects from Cohort 1 and 2 showed downstaging and finally achieved surgical complete response (CR). HF10 direct injection under EUS-guidance in combination with erlotinib and gemcitabine was a safe treatment for locally advanced pancreatic cancer. Combination therapy of HF10 and chemotherapy should be explored further in large prospective studies. This study was prospectively registered in UMIN-CTR (UMIN000010150) on March 4th, 2013.